Deep Seawater flow Characteristics Around the Manganese Nodule Collecting Device. (2015) - Lim, Sung Jin; Kim, Jong Won; Jung, Shin Taek; Cho, Hong Yeon; Lee, Sang Ho
Abstract: Flow field characteristics with outflow discharge from a collecting device in deep seawater while gathering manganese nodules have been analyzed by CFD. Numerical model is used for the analysis with CFD program of FLUENT. It is assumed that the collecting device is 4.5×5.4×6.7m with outflow speed = 1.75 m/s and the current speed = 0.1m/s.Overall seawater flow field characteristics are largely influenced by the outflow discharge from the collecting device and manganese nodule particle behavior. The outflow discharge effect reaches to about few times of the collecting device in back. As simulation results, flow velocity and streamline distributions are compared including turbulence kinetic energyvariation. This study will be useful for optimal design for manganese nodule collecting device system in deep sea.